De los litorales a las selvas : la construcción del concepto de fiebre amarilla selvática, 1881-1938 - Quevedo V., Emilio (Colección Textos (Universidad del Rosario), 2018)
This book explores the construction process of the concept of "jungle yellow fever" and the role played by Colombian researchers in this discovery. It is aimed at a general public, at academics from humanities and health sciences interested in history, history of medicine, public health, and science in particular, as well as public policy and decision-makers in health. The book presents conceptual and technical controversies in the field of yellow fever, since, the nineteenth century in Colombia until the consolidation of the concept of jungle yellow fever in the decade of 1930s. It explores how the Rockefeller Foundation ignored the analysis of Colombian doctors who hypothesized the presence of rural yellow fever and, thanks to its economic, political, and scientific power, gained primacy for discovering this concept.